2023
DOI: 10.3390/su15075865
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Responsible Tourism Perception on Place Attachment and Support for Sustainable Tourism Development: The Moderator Role of Environmental Awareness

Abstract: In this study, the effect of local people’s perceptions regarding responsible tourism on place attachment and the moderator role of environmental awareness in the effect of place attachment on support for sustainable tourism development has been determined. The research was conducted on local people in a sample of Antalya Manavgat, one of the most important tourism destinations in Turkey. The data were obtained through convenience sampling method, and the analysis was carried out with 482 questionnaires. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Contrary to current findings about the moderating role of environmental awareness, extant literature claims its positive moderating impact [100][101][102][103][104] . Similarly, studies concluded with the conditional effect of environmental awareness on connectedness to nature-organizational citizenship behavior relationship in the hotel industry [103] and place attachment-sustainable tourism development relationship in Turkey's tourism industry [105] . Along with this line, Han et al [106] concluded the positive impact of environmental awareness on young tourists' sustainable buying behaviors, recycling behaviors and intention to protect natural and local resources while travelling.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to current findings about the moderating role of environmental awareness, extant literature claims its positive moderating impact [100][101][102][103][104] . Similarly, studies concluded with the conditional effect of environmental awareness on connectedness to nature-organizational citizenship behavior relationship in the hotel industry [103] and place attachment-sustainable tourism development relationship in Turkey's tourism industry [105] . Along with this line, Han et al [106] concluded the positive impact of environmental awareness on young tourists' sustainable buying behaviors, recycling behaviors and intention to protect natural and local resources while travelling.…”
Section: Discussionmentioning
confidence: 91%
“…Government policies should focus on building tourism-conscious areas based on local wisdom and fostering local and creative industries to create awareness and entrepreneurial characteristics among the local population (Andriansyah et al 2022). The perceptions of local people regarding responsible tourism have been found to positively affect their place attachment and support for sustainable tourism development, with environmental awareness playing a moderating role (Aytekin et al 2023).…”
Section: Literature Review 11 the Concept Of Awareness And Perception...mentioning
confidence: 99%
“…Place attachment can be conceptualized as the positive psychological and emotional connections built among residents and their environment [21][22][23]. These ties are essential in planning and tourism development [24] because tourism affects not only the look of local heritages but also the values of heritages and the ties the local community have with others [18,25].…”
Section: Introductionmentioning
confidence: 99%